Efektivitas Eco Enzyme Sebagai Biokatalisator Pada Proses Anaerob Untuk Menurunkan Parameter Fosfat Limbah Laundry - Nasrullah, Nasrullahh; Junaidi, Junaidi; Nirwana, Nirwana (Teewan Solutions, 2025)
Laundry wastewater contains phosphates from detergents that can pollute the environment and cause eutrophication. This study aims to determine the effectiveness of eco enzyme as a biocatalyst in reducing phosphate levels in laundry wastewater through an anaerobic process. The eco enzyme was produced from the fermentation of fruit and vegetable peels with molasses and water, and was then applied in various concentrations. The method used in this research was a one-way factorial experimental design with a quantitative approach. Observations were conducted over 5 days, and the overall research was carried out for two months, from March 16 to May 27, 2025. Phosphate concentrations were measured using a HACH DR/2010 spectrophotometer. The results showed a decrease in phosphate levels across all concentration variations, with average reductions of 0.27 mg/L at 10% concentration, 0.25 mg/L at 20%, 0.30 mg/L at 30%, and 0.13 mg/L at 40%. The ANOVA test indicated a significant effect of eco enzyme application on phosphate reduction (p<0.05), while the LSD test revealed that the 40% concentration was the most effective dose. This study highlights the potential of organic waste materials as an environmentally friendly alternative to reduce organic waste generation and improve community environmental health. It is expected that eco enzyme can serve as a natural biocatalyst to reduce phosphate parameters in laundry wastewater treatment, making the effluent safe for discharge into the environment.